Trigonometric approximation of periodic functions in Morrey spaces using matrix means of their Fourier series - Jafarov Sadulla Z. (Mathematica Moravica)
We examine the generalized methods of summability of Fourier series of functions belonging to Morrey spaces L p,l , 0 < l ≤ 2, 1 < p < ∞. In this study, the approximation of functions by matrix means in terms of the continuity modulus in Morrey spaces L p,l , 0 < l ≤ 2, 1 < p < ∞, is investigated.